Evaluation of perinatal outcomes in pregnant women with preterm premature rupture of membranes - Souza,Alex Sandro Rolland (2016)
SUMMARY Objective: To determine the association between amniotic fluid index (AFI) and perinatal outcomes in preterm premature rupture of membranes (PPROM). Method: A retrospective cohort study was conducted between 2008 and 2012. 86 pregnant women were included, with a diagnosis of PPROM and gestational age from 24 to 35 weeks. Women who presented hypertensive disorders, diabetes, fetuses with birth defects and infection at admission were excluded. To determine the association between AFI and perinatal outcomes, chi-square and Fisher’s exact test were used if necessary, as well as risk ratio (RR) and 95% confidence intervals (95CI). Correlation between AFI and perinatal outcomes was determined by using simple linear regression, and AFI progression during pregnancy was analyzed by Z-test. Results: When comparing newborns presenting ultrasound with AFI<5cm and AFI>5cm, there was a higher frequency of perinatal mortality when the AFI was lower than 5 cm. However, when the oligohydramnios was diagnosed as severe (AFI<3cm), there was a higher frequency of Apgar scores less than seven at 1 minute, neonatal sepsis and early neonatal mortality compared to those presenting AFI>3cm. There was a positive correlation between AFI and gestational age at delivery, birth weight and Apgar scores at minutes 1 and 5. There was also a decrease in amniotic fluid volume with increased gestational age. Conclusion: The presence of severe oligohydramnios after PPROM contributed to a higher frequency of perinatal complications and death.